2018
DOI: 10.3390/f9020092
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nuclear Microsatellite Loci for Evaluating Genetic Diversity of Selected Populations of Picea abies (L.) Karsten in the Czech Republic

Abstract: DNA polymorphism at nine nuclear microsatellites of nine selected naturally-regenerated Norway spruce populations growing mainly within gene conservation units in different parts of the Czech Republic was studied. To verify the genetic quality of the selected gene conservation unit, we analyzed nine Norway spruce subpopulations from gene conservation unit GZ 102-Orlické hory. Genetic parameters can be used in state administrative decision making on including stands into gene conservation units. The level of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
4
5
1
Order By: Relevance
“…We found that the number of alleles ranged between 2 (locus Pa51) and 29 (locus WS00111.K13). Interestingly, the number of alleles for the latter EST-SSR locus was high, but similar results have been reported by other authors for the same locus; e.g., Máchová et al [47] found 34 alleles per population on the same locus, whereas Unger et al [48] and Cvjetković et al [49] reported 28 and 20 alleles per population on this locus, respectively.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…We found that the number of alleles ranged between 2 (locus Pa51) and 29 (locus WS00111.K13). Interestingly, the number of alleles for the latter EST-SSR locus was high, but similar results have been reported by other authors for the same locus; e.g., Máchová et al [47] found 34 alleles per population on the same locus, whereas Unger et al [48] and Cvjetković et al [49] reported 28 and 20 alleles per population on this locus, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…Likewise, a very low overall genetic differentiation among studied Norway spruce populations in Serbia was detected (0.007). The observed value of F st was lower than it was previously reported for this species using genomic SSR (F st = 0.050, [44]; F st = 0.088, [53]; F st = 0.029, [43]), EST-SSRs (F st = 0.026, [49]), and a combination of genomic and EST-SSR markers (F st = 0.011, [47]). On the other hand, genetic differentiation among Serbian populations was higher than Unger et al [48] reported for three Tyrol populations (F st = 0.002) using EST-SSR markers and Westergren et al [46] for Slovenian core and marginal populations (F st = 0.002), using genomic SSRs.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…In our study, the estimated parameters of mean heterozygosity (Ho = 0.601, He = 0.705) are comparable to previously published studies [34,[66][67][68][69][70]; similarly, in our case, these are accompanied by a low level of genetic differentiation among populations. Similar values were observed despite the variety of experimental and sampling design, targeting various features and traits of interest.…”
Section: Discussionsupporting
confidence: 91%